2002
DOI: 10.1345/aph.1c095
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Induced Myopathy in the ICU

Abstract: Steroid-induced myopathy is a complication of high-dose steroid use. Unfortunately, in this patient, initial treatment of status asthmaticus required intravenous steroids in high doses to adequately treat the presenting illness. Clinicians should be aware of neuromuscular findings and act aggressively to appropriately eliminate systemic steroids from the treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The correlation between steroid treatment and dyspnoea scale and some respiratory functional values appear to be independent from pneumonia severity and could reflect the contribute of steroid to viral myopathy through several mechanisms, such as altered electrical excitability of muscle fibres, loss of thick filaments and inhibition of protein synthesis [18][19][20], even if MIP and MEP didn't prove this relation.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between steroid treatment and dyspnoea scale and some respiratory functional values appear to be independent from pneumonia severity and could reflect the contribute of steroid to viral myopathy through several mechanisms, such as altered electrical excitability of muscle fibres, loss of thick filaments and inhibition of protein synthesis [18][19][20], even if MIP and MEP didn't prove this relation.…”
Section: Discussionmentioning
confidence: 99%
“…11,[18][19][20] Biopsies of skeletal muscle showed variation in muscle fibre size, atrophy, and necrosis. 11,21 One study 22 on steroidinduced myopathy in rabbits showed changes as early as 4 h after cortisone injections to one lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…However, use of neuromuscular blockers should be discontinued as soon as feasible to reduce the likelihood of prolonged muscle weakness from the interaction of these agents and corticosteroids. ( 76 , 77 ) We prefer to use cisatracurium because it does not contain the corticosteroid-like moiety found in vecuronium and rocuronium that is thought to explain the association between myopathy and co-therapy with both corticosteroids and aminosteroid-based neuromuscular antagonists. ( 76 , 77 )…”
Section: Intubation Analgesia Sedation and Muscle Relaxationmentioning
confidence: 99%